Ivy + Bean - Barrows, Annie; Blackall, Sophie (San Francisco : Chronicle Books, 2007)
Bean wasn't interested in making friends with Ivy, the new girl across the street, until she plays a trick on her sister and needs a place to hide out.
Notable/Best Books (A.L.A.)
School Library Journal
Wilson's Children
Book Links (A.L.A.), September 2006
Booklist starred, April 2006
Bulletin (Center for Children's books), June 2006
Keywords: Friendship -- Juvenile fiction; Neighbors -- Juvenile fiction; Friendship -- Fiction; Neighbors -- Fiction; Friendship -- Fiction; Neighbors -- Fiction